Threshold concepts in the teaching of natural sciences: A systematic review - Jaime Solís Pinilla; Cristian Merino Rubilar (OmniaScience, 2024)
A systematic review of Threshold Concepts provides a thorough and structured analysis of the existing literature related to these essential and transforming concepts in education. Threshold Concepts represent ideas or knowledge that, once understood, allow the student to access deeper levels of understanding of a discipline. These concepts are crucial, since they act as "doors" that, once "crossed", lead to a more integrated and coherent vision of a study area. In the review, various academic databases were consulted to identify relevant studies, applying rigorous inclusion and exclusion criteria. Through this process, key patterns, methodologies, and findings were detected, related to the teaching, understanding and application of these concepts. Despite the broad methodological diversity that exists in the field, as well as educational approaches and contexts, Threshold Concepts are not always addressed successfully at the curricular level or in the implementation of teaching methodologies. The limitations of this review have an impact on possible publishing bias and the diversity of research methods. However, the review stresses the need for greater integration of these concepts in education, as well as future research that explores efficient pedagogical strategies to teach them.